Efficacy and safety of basic fibroblast growth factor (bFGF) related decapeptide solution plus Tacrolimus 0.1% ointment versus Tacrolimus 0.1% ointment in the treatment of stable vitiligo. Issue 6 (24th October 2019) - Shah, Bela; Godse, Kiran; Mahajan, Satyaprakash; Grandhi, Sudhakarrao; Shendkar, Sonal; Sharma, Akhilesh; Teli, Chirag; Pathak, Rahul; Parsad, Davinder
Abstract: Vitiligo is common acquired pigmentary disorder affecting skin of 1% of the world population, India 3% to 8% incidences approximately. Treatment is tough challenge. The combination treatments have proven beneficial due to different mechanisms. There is need to find drug targeting different mechanisms of action. Test medicine is decapeptide derived from basic Fibroblast Growth Factor (bFGF) treating vitiligo. The current study was to compare efficacy and safety of BFGF related decapeptide solution plus Tacrolimus 0.1% (M + T) Ointment versus Tacrolimus monotherapy 0.1% (T) Ointment in patients with stable vitiligo. The randomized, open label, comparative, prospective, multicentre study in patients with stable vitiligo was conducted. The primary endpoint was improvement in extent of repigmentation in target lesion after 12 months of treatment from baseline. The secondary endpoints were extent of repigmentation at end of 6 months, patient global assessment (PGA) and safety at end of 6 months. This shows interim analysis results. Total 94 patients were randomized to M + T ( n = 40) and T ( n = 44), 10 patients were lost to follow up. Extent of repigmentation (>50%) was significantly greater at end of 8 weeks in M + T group 22.5% ( p  ≤ .05) while 6.8% in T group. In grade of repigmentation, significant difference ( p  ≤ .05) was observed, M + T had better grade. PGA was significantly greater ( p  ≤ .05) in M + T‐group than T. All these parameters showed significant improvement in M + T‐group than group T at end of 6 months. No adverse events were reported during the study. It is an interim analysis report so complete data is not available for analysis. Addition of bFGF related decapeptide solution to Tacrolimus gave better results than Tacrolimus alone therapy. It also has a favorable safety profile and was well tolerated.